Photonic-Delay Line Cross Correlation Method Based on DWDM for Phase Noise Measurement - Zhiqiang Fan (IEEE Photonics Journal, 2018)
A dual photonic-delay line cross-correlation method for phase noise measurement of microwave signal based on dense wavelength division multiplexing (DWDM) is proposed and experimentally demonstrated. The kilometer-long delay fiber is used together by the two mutually independent channels through the DWDM technology, which makes it easier to get the same delay between two channels. And it reduces the cost of the system by reducing the use of several kilometers of fiber and a Mach-Zendher modulator. Then, it uses variable optical fiber delay lines to replace the electronic phase shifters and a broader operation bandwidth can be obtained. A lower phase noise floor has been obtained by more averaging of the cross-correlation spectrum. In the experiments, the phase noise of a 10-GHz microwave signal has been measured accurately. A large operation bandwidth of 4-11 GHz is achieved and a measurement phase noise floor of -152.6 dBc/Hz at 10 kHz offset at 10 GHz in a 20 μs delay measurement system is realized by averaging 100 times.